Expression and Study of Recombinant ExoM, a β1-4 Glucosyltransferase Involved in Succinoglycan Biosynthesis in Sinorhizobium meliloti - Lellouch, Annemarie C. (American Society for Microbiology, 1999)
Here we report on the overexpression and in vitro characterization of a recombinant form of ExoM, a putative β1-4 glucosyltransferase involved in the assembly of the octasaccharide repeating subunit of succinoglycan from Sinorhizobium meliloti. The open reading frame exoM was isolated by PCR and subcloned into the expression vector pET29b, allowing inducible expression under the control of the T7 promoter. Escherichia coli BL21(DE3)/pLysS containing exoM expressed a novel 38-kDa protein corresponding to ExoM in N-terminal fusion with the S-tag peptide. Cell fractionation studies showed that the protein is expressed in E. coli as a membrane-bound protein in agreement with the presence of a predicted C-terminal transmembrane region. E. coli membrane preparations containing ExoM were shown to be capable of transferring glucose from UDP-glucose to glycolipid extracts from an S. meliloti mutant strain which accumulates the ExoM substrate (Glcβ1-4Glcβ1-3Gal-pyrophosphate-polyprenol). Thin-layer chromatography of the glycosidic portion of the ExoM product showed that the oligosaccharide formed comigrates with an authentic standard. The oligosaccharide produced by the recombinant ExoM, but not the starting substrate, was sensitive to cleavage with a specific cellobiohydrolase, consistent with the formation of a β1-4 glucosidic linkage. No evidence for the transfer of multiple glucose residues to the glycolipid substrate was observed. It was also found that ExoM does not transfer glucose to an acceptor substrate that has been hydrolyzed from the polyprenol anchor. Furthermore, neither glucose, cellobiose, nor the trisaccharide Glcβ1-4Glcβ1-3Glc inhibited the transferase activity, suggesting that some feature of the lipid anchor is necessary for activity.